A Branching Narrative 2D Action RPG Game to Enhance Learning About the Ambarawa Battle - Laudy Nurdibya Nandaru; Chrystia Aji Putra; Andreas Nugroho Sihananto (Komunitas Dosen Indonesia, 2026)
This study develops a historical educational game titled Pertempuran Ambarawa to address the persistent challenge of low student engagement and limited contextual understanding in history classrooms, where learning is often dominated by memorization-based instruction. To provide a more interactive and reflective learning experience, the game integrates a branching narrative structure, 2D action RPG mechanics, and stealth–strategy minigames within the Interactive Digital Narrative (IDN) framework. This approach is intended to enhance learners’ historical reasoning by situating them in decision-based scenarios that mirror the complexities of the Ambarawa Battle. The game was implemented in Unity with 2D pixel-art aesthetics and evaluated through a pre-test–post-test design involving 25 junior high school students. Results show a significant improvement in historical comprehension, with mean scores increasing from 59.2 to 79.2 and the Wilcoxon Signed-Rank test yielding p = 0.00077 (p < 0.05). User experience was assessed using the GUESS-18 instrument, achieving an overall rating of 4.29 (Very Good), with the Education and Branching Narrative dimensions receiving the highest scores. These findings indicate that narrative interactivity and contextualized gameplay meaningfully contribute to learning effectiveness. Overall, the study demonstrates that combining branching narratives with RPG-based exploration provides a compelling alternative learning medium, offering both pedagogical value and strong user acceptance in history education.